Resilience : the science of mastering life's greatest challenges - Southwick, Steven M.; Charney, Dennis S. (Cambridge University Press, 2012)
"Many of us will be struck by one or more major traumas sometime in our lives. Perhaps you have been a victim of sexual abuse, domestic violence or assault. Perhaps you were involved in a serious car accident. Perhaps you are a combat veteran. Maybe you were on the beach in Thailand during a tsunami, or in New Orleans during Hurricane Katrina. Or maybe, you are among the millions who have suffered a debilitating disease, lost a loved one or lost your job. This inspiring book identifies ten key ways to weather and bounce back from stress and trauma. Incorporating the latest scientific research and dozens of interviews with trauma survivors, it provides a practical guide to building emotional, mental and physical resilience. Written by experts in post-traumatic stress, this book provides a vital and successful roadmap for overcoming the adversities we all face at some point in our lives"-- Provided by publisher